Determinants of saving behavior among the students at Universiti Putra Malaysia - Jaffar, Muhamad Wafiy Asnawi; Md Jusoh, Zuroni; Mohamed, Rozita Naina (Jurnal Terbitan Persatuan Ekonomi Pengguna Dan Keluarga Malaysia, 2022)
This study aimed to determine the relationship between financial literacy, parental socialization, peer influence, self-control, and saving behavior among the students at Universiti Putra Malaysia. Two hundred fifty students from Universiti Putra Malaysia were selected via simple random sampling. A questionnaire was used to collect the quantified research data. The data obtained were analyzed using SPSS software version 26. Pearson correlation is used to determine the relationship between variables, and Multiple Linear Regression is used to examine the relationship between one dependent variable and several independent variables. The findings show that there was a significant relationship between parental socialization (r= r = 0.532**, p = 0.000), a significant relationship between financial literacy and saving behaviour (r = 0.425**, p = 0.000), a significant relationship between self-control and saving behaviour (r = 0.271**, p = 0.000), and a significant relationship between peer influence and saving behaviour (r = 0.266**, p = 0.000). Multiple Linear Regression analysis also found that financial literacy, parental socialization, peer influence, and self-control had a significant relationship with saving behavior (R2 = 0.382, F = 37.806, and p < 0.05). In conclusion, all the independent variables are significant in saving behavior. The study contributed significantly to assisting the retail banks and policymakers in providing the students with sufficient knowledge about saving and reducing bad attitudes and behaviors. Retail banks and policymakers should establish an effective education program based on students' needs and level of financial literacy. Parents must encourage their children to save, which will positively impact their future lives and personal well-being.